(untitled) (Revista Internacional de Folkcomunicação, 2023)
The purpose of this paper is to examine the use of mobile communication technologies by elderly people with low literacy, articulating the folk communication perspective by identifying the group’s obstacles and limitations in accessing information, as well as the search for alternative ways to use the available technology. The data acquired through interviews with members of groups for Fortalecimento de Vínculos da Terceira Idade (Strengthening Third Age Links), sponsored by the Centros de Referência de Assistência Social (Social Assistance Reference Centers) in the Curitiba Metropolitan Region (Paraná, Brazil), are the subject of the study. Bibliographic research is used to investigate the interaction between the elderly and the Internet, as well as literacy and digital literacy. The data analysis reveals that the group discovers its own methods to benefiting from technology, but makes little use of options other than leisure and instant messaging.